Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Anggota Oriflame Indonesia - Jublina Oktora; Rahmi Andini Syamsuddin (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
The object of this study is to determine the impact of the work environment and motivation on the performance of members of Oriflame Indonesia. In this study, using a proportional random sampling technique, namely by using a sample of 91 respondents. Methods of data analysis using regression analysis, correlation coefficient analysis, analysis of the coefficient of determination, and hypothesis testing. Based on the partial test results for work environment variables obtained t = 2.756 with a significance value of 0.007, then Ho is rejected, and Ha is accepted. This shows that partially H1, which states that there is an influence of the work environment on performance, is accepted. Based on the partial test results for the motivation variable, it was obtained t = 3.405 with a significance value of 0.001 because the significant probability is much smaller than 0.05 then Ho is rejected, and Ha is accepted. This shows that partially H2, which states that there is an effect of motivation on performance, is accepted. Based on the test results on the F test, it is obtained that the value of F count> F table or (21.255 > 2,720), this is also reinforced by ρ value < Sig. 0.05 or (0,000 < 0.05). Thus, H0 is rejected, and H3 is accepted, this indicates that there is a positive and significant influence simultaneously between Work Environment and Motivation on the performance of Oriflame Member